(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article analyzes the characters of the epic work with the oriental motifs, widely spread in Kazakh folklore. Speaking about the wide spread of the epos «Leyli-Majnun» among the people, about its teaching value not only about sincere love, but also about such qualities as patience and endurance, the author reports the direction of he image of the main heroes of the epic. This article is part of the scientific project devoted to the problem of unification of folklore characters, in this connection the author in the article raises the problem «How should images of Layla and Majnun be represented?». Moreover, it is said that it is necessary to pay close attention not only to the language of the work, artistic features and poetics, but also to the inner content, time and place of happenings. The qualities of the epic characters such as benevolence, determination and trust have a special educational significance for young people in our days. It must be said that the importance of the acquaintance of the young generation with such valuable works, the transfer of the image characters described in words, is very large.